Adolescent Male Sports Participation and Violence in Emerging Adulthood: Examining Variation by Gender-Typed Behavior. Issue 11 (2nd November 2019) - Finkeldey, Jessica G.
ABSTRACT: Research on the association between sports participation and violence is mixed. Moreover, most studies that recognize some sport subcultures equate masculinity with violence have not included indicators of adherence to gender-typed behaviors. The current study used the National Longitudinal Study of Adolescent to Adult Health to investigate the association between male adolescent sports participation and violence in young adulthood, as well as the degree to which this relationship varied by adherence to gender-typed behaviors. Analyses revealed that male adolescent sports participation was positively associated with violence during emerging adulthood, particularly for those who displayed gender-atypical (i.e., more feminine) behaviors.